Effects of Low‐Level Laser Therapy (LLLT) and Diclofenac (Topical and Intramuscular) as Single and Combined Therapy in Experimental Model of Controlled Muscle Strain in Rats. (8th November 2012) - de, Rodrigo Leal; Leal‐Junior, Ernesto Cesar Pinto; Petrellis, Maria Carla; Marcos, Rodrigo Labat; de, Maria Helena Catelli; De, Gilberto; Lopes‐Martins, Rodrigo Alvaro Brandão
Abstract Muscle injuries represent ca 30% of sports injuries and excessive stretching of muscle causes more than 90% of injuries. Currently the most used treatments are nonsteroidal anti‐inflammatory drugs (NSAIDs), however, in last years, low‐level laser therapy (LLLT) is becoming an interesting therapeutic modality. The aim of this study was to evaluate the effect of single and combined therapies (LLLT, topical application of diclofenac and intramuscular diclofenac) on functional and biochemical aspects in an experimental model of controlled muscle strain in rats. Muscle strain was induced by overloading tibialis anterior muscle of rats. Injured groups received either no treatment, or a single treatment with topical or intramuscular diclofenac (TD and ID), or LLLT (3 J, 810 nm, 100 mW) 1 h after injury. Walking track analysis was the functional outcome and biochemical analyses included mRNA expression of COX‐1 and COX‐2 and blood levels of prostaglandin E2 (PGE2). All treatments significantly decreased COX‐1 and COX‐2 gene expression compared with injury group (P < 0.05). However, LLLT showed better effects than TD and ID regarding PGE2 levels and walking track analysis (P < 0.05). We can conclude that LLLT has more efficacy than topical and intramuscular diclofenac in treatment of muscle strain injury in acute stage.